Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Fuli Yu; Jian Lu; Xiaoming Liu; Elodie Gazave; Diana Chang; Srilakshmi Raj; Haley Hunter-Zinck; Ran Blekhman; Leonardo Arbiza; Cris Van Hout; Alanna Morrison; Andrew D Johnson; et al. (PLoS ONE)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.